Central Nervous System Manifestations in Diabetes Mellitus - A Review - Acherjya, Goutam Kumar; Uddin, Md Moslem; Chowdhury, MA Jalil; Srinivasan, AV (Journal of Medicine, 2017)
The impact of diabetes mellitus on the CNS (Central Nervous System) has gained attention only recently. Peripheral neuropathy has been the primary neuroscience focus of diabetes research. Contrary to some early impressions, however, the CNS is not spared by diabetes. Chronically, diabetes mellitus affects the CNS in several ways. Diabetes increases stroke risk and damage, overtreatment with insulin or oral agents can permanently damage the brain, and diabetes may increase the prevalence of seizure disorders. Diabetes changes brain transport, blood flow and metabolism, and may produce a chronic encephalopathy. Acutely, glycemic extremes cause coma, seizures, focal neurolclgical deficits, and impaired consciousness. The pathophysiological basis for these marked CNS abnormalities seen in hypoglycemia, hyperosmolar coma, and ketoacidosis are largely unknown. Methods: This review was based on a search of Pubmed, the NCBI Database of systemic Reviews, and citation lists of relevant publications. Subject heading and key words used central nervous system, diabetes mellitus, stroke, encephalopathy and hypoglycaemia. Only articles in English were included. J MEDICINE July 2017; 18 (2) : 109-112